"STATE FINANCIAL/ASSET RECOVERY IN CORRUPTION AND MONEY LAUNDERING CRIMES: REORIENTING THE GOALS OF PUNISHMENT TOWARDS DOEL THEORIEN" - Raisatul Karimah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The escalation of corruption and money laundering cases and their loss need to be responded by reorienting the objectives of criminalizing corruption and money laundering cases towards doel theorien which emphasizes the aspect of state financial/asset recovery and restoration. By using the juridical-normative research method, the results obtained were there are three challenges faced by law enforcement in Indonesia in carrying out and optimizing state financial/asset recovery in corruption and money laundering, namely: 1) the criminalization system for corruption and money laundering tends to focus on retaliation (punitive) against the perpetrators; 2) there is complexity in technology and financial/banking systems; and 3) limited international cooperation in combating corruption and money laundering. In terms of re-orientation of the purpose of punishment towards doel theorien in corruption and money laundering, law enforcement can be carried out through two main ideas, namely 1) by optimizing the Double Track System in Corruption and Money Laundering in corruption and money laundering cases to return state assets and finances resulting from corruption and other crimes; and 2) doel theorien in corruption and money laundering is oriented towards restoration efforts, one of which is by introducing the Pre-Trial Conference in state financial/asset recovery efforts.